2018
DOI: 10.1590/s2175-97902017000400010
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and dissolution enhancement of flurbiprofen by solid dispersion using hydrophilic carriers

Abstract: The intent of the current work is to study the effect of polyethylene glycol 8000 and polyethylene glycol 10000 as hydrophilic carriers on dissolution behaviour of flurbiprofen. In the present study, solvent evaporation method was used to prepare flurbiprofen solid dispersions and evaluated for physicochemical properties, drug-carrier compatibility studies and dissolution behaviour of drug. Solubility studies showed more solubility in higher pH values and formulations SD4 and SD8 were selected to prepare the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Ketoprofen’s solubility in PBS was within the range reported by Cayman (500 mg/L) [ 60 ] and Shohin et al (3310 mg/L) [ 61 ] but lower than the one of Felton et al [ 56 ]. For flurbiprofen, the determined PBS solubility was in accordance with Sadik et al (130 ± 40 mg/L) [ 62 ] and Daravath et al (98 ± 10 mg/L) [ 63 ], despite the heterogeneity of values reported (98 to 4445 mg/L) [ 56 , 62 , 63 , 64 , 65 ]. The value obtained for naproxen was in agreement with Cayman (1000 mg/L) and Kumar et al (750 ± 250) mg/L, being lower than Felton and co-authors’ value (4259 mg/L).…”
Section: Resultssupporting
confidence: 85%
“…Ketoprofen’s solubility in PBS was within the range reported by Cayman (500 mg/L) [ 60 ] and Shohin et al (3310 mg/L) [ 61 ] but lower than the one of Felton et al [ 56 ]. For flurbiprofen, the determined PBS solubility was in accordance with Sadik et al (130 ± 40 mg/L) [ 62 ] and Daravath et al (98 ± 10 mg/L) [ 63 ], despite the heterogeneity of values reported (98 to 4445 mg/L) [ 56 , 62 , 63 , 64 , 65 ]. The value obtained for naproxen was in agreement with Cayman (1000 mg/L) and Kumar et al (750 ± 250) mg/L, being lower than Felton and co-authors’ value (4259 mg/L).…”
Section: Resultssupporting
confidence: 85%
“…Here, the effect of a drug to carrier ratio on solubility was studied and it was found that a 1:2 ratio gave maximum solubility of meloxicam in distilled water. Higher is the molecular weight, higher is the solubility [22]. Therefore, PEG-15,000 was found to be more effective in enhancing solubility than PEG-6000 based on molecular weight.…”
Section: Solubility Study Of Solid Dispersionmentioning
confidence: 97%
“…The drug content estimated spectrophotometrically at 247nm. [15][16][17] Release Kinetic Study Different kinetic models such as zero order, first order, Higuchi, and Korsmeyer-Peppa's were used to infer the drug release rate from the buccal patches comprising of flurbiprofen solid dispersions. The drug release data was substituted in various kinetic models to envisage the kinetics and mechanism.…”
Section: In Vitro Release Studymentioning
confidence: 99%